A global map of Amenities: Public Goods, Ethnic Divisions and Decentralization - André Seidel (ZBW - Leibniz Information Centre for Economics, 2020)
I analyze the effects of ethnic divisions on the provision of public goods. Using OpenStreetMap data, I construct a new global dataset of locations of public amenities, such as schools, hospital and libraries. I allow for the possibility that the data may be systematically incomplete using two new proxies for mapping completeness. I provide strong evidence that more autonomous subnational regions with a high degree of ethnic fractionalization provide significantly fewer productive public goods. Therefore, my findings indicate that decentralization can lead to a failure in the provision of local public goods when it increases ethnical fractionalization among the policy makers responsible for collectively supplying public goods.
Keywords: H41; H77; H75; D72; R53; C82; 330; public goods; amenities; decentralization; ethnic fractionalization; OpenStreetMap